Text book of criminal law ( Indian penal code). - "Mani, B.N." (Allahabad, 1996)
This book is a commentary on Indian Penal Code. It also includes discussion of fundamentals of criminology. It is a short but comprehensive book on the subject. Though it is meant for LL. B. students, it equally useful for the students preparing for various competitive examinations and all those who are interested in the study of the subject. In preparing the commentary held has been taken from the commentaries on Indian Penal Code by Ratanlal & Dhirajlal, Hari Singh Gaur and R. C. Nigam's book 'Law of Crimes in India', Huda's 'Principles of Criminal Law'.
Keywords: Criminal law